2006
DOI: 10.1124/jpet.105.098558
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Renal Cytochrome P450 Arachidonic Acid Epoxygenase Activity by Dietary γ-Linolenic Acid

Abstract: Dietary ␥-linolenic acid (GLA), a -6 polyunsaturated fatty acid found in borage oil (BOR), lowers systolic blood pressure in spontaneously hypertensive rats (SHRs). GLA is converted into arachidonic acid (AA) by elongation and desaturation steps. Epoxyeicosatrienoic acids (EETs) and 20-hydroxyeicosatetraenoic acid (20-HETE) are cytochrome P450 (P450)-derived AA eicosanoids with important roles in regulating blood pressure. This study tested the hypothesis that the blood pressure-lowering effect of a GLA-enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…P450 epoxygenases are induced by dietary fatty acids and during hypertension, but there is no evidence for selective induction of these enzymes by small molecules, including cisplatin (Yu et al, 2000a(Yu et al, , 2006. Induction of P450 epoxygenases as a viable approach for increasing EETs is therefore of limited use.…”
Section: Discussionmentioning
confidence: 99%
“…P450 epoxygenases are induced by dietary fatty acids and during hypertension, but there is no evidence for selective induction of these enzymes by small molecules, including cisplatin (Yu et al, 2000a(Yu et al, , 2006. Induction of P450 epoxygenases as a viable approach for increasing EETs is therefore of limited use.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EETs or 20-HETE generated in liver or in extrahepatic organs such as the gastrointestinal tract or kidney, where TCDD-inducible CYP1A2 and PB-inducible CYP2 enzymes are present (Ding and Kaminsky, 2003;Yu et al, 2006), could have systemic as well as local effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the modulation of renal and hepatic P450-mediated arachidonic acid metabolism in several pathophysiological and experimental conditions, most notably fasting, increased dietary ␥-linolenic acid, and inflammation (Qu et al, 1998;Yu et al, 2006;Anwar-Mohamed et al, 2010;Theken et al, 2011). However, there is little information about the effect of DOX toxicity on the expression of P450 enzymes in the kidney and liver.…”
Section: Introductionmentioning
confidence: 97%